Adult presentation of Bartter syndrome type IV with erythrocytosis - Heilberg, Ita P feferman (2018)
Bartter syndrome comprises a group of rare autosomal-recessive salt-losing disorders with distinct phenotypes, but one unifying pathophysiology consisting of severe reductions of sodium reabsorption caused by mutations in five genes expressed in the thick ascending limb of Henle, coupled with increased urinary excretion of potassium and hydrogen, which leads to hypokalemic alkalosis. Bartter syndrome type IV, caused by loss-of-function mutations in barttin, a subunit of chloride channel CLC-Kb expressed in the kidney and inner ear, usually occurs in the antenatal-neonatal period. We report an unusual case of late onset presentation of Bartter syndrome IV and mild phenotype in a 20 years-old man who had hypokalemia, deafness, secondary hyperparathyroidism and erythrocytosis.